The Reversely Zoned Castelo Branco Pluton at the New “Barrocal” City Park (Central Iberian Zone, Portugal) - Isabel Margarida Antunes; Carlos de Carvalho; Mohamed Abioui (Geoconservation Research)
The "Barrocal" city Park of Castelo Branco is an urban park developed to protect the geoheritage of the tardi-Variscan granite landscapes of the only city existing in the area of the Naturtejo UNESCO Global Geopark. The "Barrocal" Granite is part of a Late Carboniferous unusual reversely zone intrusion with a granodiorite core and different granites in the rim. The weathering processes developed many textbook examples of granite landforms that are now accessible and available for appreciation by the local community and tourists in a 40 ha park, the newly geotourist attraction of the Geopark.